PDR Indoor Positioning Method Based on M2M Encounter Region - TANG Qing-hua, WANG Mei, TANG Chao-chen, LIU Xin, LIANG Wen (Jisuanji kexue, 2022)
In indoor positioning,the main advantage of pedestrian dead reckoning(PDR)is that the user only needs to have a smart phone to realize positioning,without relying on the external environment.However,there is a large cumulative error.Ge-nerally,it is necessary to combine Bluetooth,WiFi,geomagnetic or other technologies to improve the positioning accuracy.How-ever, this method requires some hardware nodes and a fingerprint database to be built for this purpose.To solve this problem,an indoor positioning method based on correcting PDR in machine to machine(M2M)area is proposed.Firstly,a distance measurement area is set up during pedestrian travel.Secondly,the distance between pedestrian mobile phones and other mobile phones is measured in this region.Finally,the positioning error and accuracy of PDR are corrected by trilateral positioning method.The method has the advantages that no additional hardware facilities are required.Experimental results show that,compared with the traditional PDR positioning,this method is suitable for long-time positioning,and the average positioning error is reduced to 0.36 m,with high positioning accuracy.